2021
DOI: 10.3389/fphar.2021.669370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Monoamine Oxidase Inhibitors on Anxiety-Like Behavior in Zebrafish

Abstract: Monoamine oxidases (MAO) are a valuable class of mitochondrial enzymes with a critical role in neuromodulation. In this study, we investigated the effect of natural MAO inhibitors on novel environment-induced anxiety by using the zebrafish novel tank test (NTT). Because zebrafish spend more time at the bottom of the tank when they are anxious, anxiolytic compounds increase the time zebrafish spend at the top of the tank and vice versa. Using this paradigm, we found that harmane, norharmane, and 1,2,3,4-tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…ALT and AST are enzymes mainly confined within the hepatocytes, although they are also found in the heart, kidney, blood cells and pancreas (Aja et al 2020) while monoamine oxidase is a mitochondrial enzyme with high activity in the brain, GIT and hepatic tissue (Jaka et al (2021). CCl 4 significantly increased the serum activities of ALT, AST and MAO compared to normal control.…”
Section: Effect Of Apg On Liver Function Indicesmentioning
confidence: 99%
“…ALT and AST are enzymes mainly confined within the hepatocytes, although they are also found in the heart, kidney, blood cells and pancreas (Aja et al 2020) while monoamine oxidase is a mitochondrial enzyme with high activity in the brain, GIT and hepatic tissue (Jaka et al (2021). CCl 4 significantly increased the serum activities of ALT, AST and MAO compared to normal control.…”
Section: Effect Of Apg On Liver Function Indicesmentioning
confidence: 99%
“…Norsolorinic acid [105 ] Averufin Another notable naphthoquinone, 2,3,6-trimethyl-1,4-naphthoquinone 110, was extracted and isolated from cured tobacco leaves (Nicotiana tabacum) and was found to be a competitive inhibitor of human MAO (human liver mitochondrial preparation) with Ki values of 3 and 6 μM for MAO-A and MAO-B, respectively [168]. Recent studies found using a human MAO assay that 110 inhibited MAOs with IC50 values of 1.14 and 7.14 μM for MAO-A and MAO-B, respectively [169]. The same authors evaluated the anxiolytic effects of 110 on a zebrafish model, describing that the compound induced anxiolytic and anxiogenic-like effects on the model tested [169].…”
Section: Mao Inhibitory Activity Of Xanthones Anthraquinones and Naph...mentioning
confidence: 99%
“…Recent studies found using a human MAO assay that 110 inhibited MAOs with IC50 values of 1.14 and 7.14 μM for MAO-A and MAO-B, respectively [169]. The same authors evaluated the anxiolytic effects of 110 on a zebrafish model, describing that the compound induced anxiolytic and anxiogenic-like effects on the model tested [169]. Menadione 111, a naphthoquinone formed by metabolism from the dietary vitamin K (menaquinones), was reported as selective MAO-B inhibitor with a Ki value of 0.4 μM [170].…”
Section: Mao Inhibitory Activity Of Xanthones Anthraquinones and Naph...mentioning
confidence: 99%
“…The disturbance of monoamine transmitters plays an important role in mood disorders, and the suppression of monoamine oxidase (MAO) can improve mood disorders such as anxiety [ 66 , 67 , 68 ]. A recent finding demonstrated that monoamine oxidase inhibitor (MAOI) also exhibits a neuroprotective effect [ 69 ] and improves memory [ 70 , 71 ]. Obesity, one of the components of metabolic syndrome, increases MAO [ 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%